Presence of acute ischaemic lesions on diffusion-weighted imaging is associated with clinical predictors of early risk of stroke after transient ischaemic attack. - Redgrave, J; Schulz, U; Briley, D; Meagher, T; Rothwell, P (2007)
BACKGROUND: Early risk of stroke after a transient ischaemic attack (TIA) can be reliably predicted with risk scores based on clinical features of the patient and the event, but it is unclear how these features correlate with findings on brain imaging and few studies have investigated this in the subacute phase. METHODS: Two hundred consecutive patients attending a specialist clinic underwent diffusion-weighted brain imaging (DWI) on the day of the clinic (> or =3 days after a TIA) and the presence of recent lesions (positive DWI) was related to the presence of clinical features associated with a high stroke risk and to 2 validated risk scores (ABCD and California). RESULTS: Thirty-one patients (16%) had positive DWI. Increasing ABCD and California scores were associated with positive DWI (p = 0.02 for both) independent of the delay from TIA to scan. CONCLUSION: Presence of recent ischaemic lesions on DWI correlates with validated clinical scores for risk of stroke after TIA in patients scanned subacutely. Future prognostic studies of DWI after TIA should adjust for the risk scores to determine the independent predictive value of DWI and hence the likely role of DWI in refinements of the scores.